Direct reduction of vanadium titanium pellets using ammonia as a reductant: Thermodynamics, characteristics, and kinetics analysis - Yuejun Liu; Xianchun Li; Shaoyan Wang; Li Li (Fuel Processing Technology)
Applying hydrogen (H2) as a reductant can decrease the difficulty of reducing vanadium titanium ores. However, using ammonia (NH3) instead of H2 as a reductant can solve the problem of difficult storage and transportation of H2. Here, we investigated the reaction characteristics and isothermal kinetics of the vanadium titanium pellets (V1) ores reduced by NH3 using high-thermogravimetric equipment at temperatures ranging from 875 °C to 950 °C. A thermodynamic analysis was conducted on the reaction of NH3 and H2 reducing V1 ores. The thermodynamic results indicated that the reaction of NH3 reducing V1 ores is more spontaneous compared to H2, demonstrating the superiority of NH3 as a reductant. A metallization rate of 95.59 % at a temperature of 950 °C, an NH3 concentration of 60 %, and a reduction time of 180 min. The highest concentration of nitric oxide (NO) during the reduction process can reach 198 ppm, and NO will gradually decrease as the reaction progresses. The apparent activation energies for the reduction of V1 ores by 60 % NH3 obtained by the model-fitting method and model-free method were 151.43 kJ/mol and 150.44 kJ/mol, respectively. This study provides theoretical support for deeper understanding of the process of NH3-reducing vanadium titanium pellets.